Incidence and risk factors of active carbapenem-resistant enterobacteriaceae surveillance in hematology patients: a propensity score matching study - Chen, Shaozhen; Fan, Jixin; Xiao, Tingting; Ren, Jinhua; Zhu, Haojie; Kong, Hui; Chen, Dabing; Xu, Jingjing; Ye, Chenjing; Sun, Jiaqi; Hu, Caidong; Zheng, Xiaoyun; et al. (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Enterobacteriaceae (CRE) infections pose a significant threat to hematological patients, contributing to high mortality rates. This retrospective study evaluated the incidence, risk factors, and patient outcomes associated with active CRE surveillance in the hematology department.MethodsThe study identified 23,832 hematological patients between 2019 and 2021. Propensity score matching was used to align underlying diseases and admission times in a 1:1:1 ratio across three groups: detected CRE, undetected CRE, and non-active CRE surveillance. The positivity rate of active CRE surveillance was 2.1% (141/6,735), with an incidence of 4.8% (85/1,789) among patients who underwent active CRE surveillance.ResultsThe distribution of the 141 isolates was as follows: Klebsiella pneumoniae (66.7%), Escherichia coli (22.6%), and others (10.7%). Independent risk factors associated with a positive result for active CRE surveillance included hematopoietic stem cell transplantation, hospital length of stay (LOS) ≥ 18 days, use of central venous catheters, steroid treatment within the past 3 months, antibiotic exposure (ß-lactam/ß-lactamase inhibitor, Echinocandins) within the last month, perianal skin ulceration within the previous 3 days, albumin < 33.4 g/L, and neutropenia lasting ≥ 7 days. In the detected CRE group, 26.5% of patients developed a CRE infection. Cox regression analysis identified diarrhea within 3 days prior to active CRE surveillance and interleukin-6 levels ≥ 39.35 pg./mL within 24 h of CRE surveillance as independent predictors of 90-day mortality. Klebsiella pneumoniae and Escherichia coli were the predominant pathogens identified in active CRE surveillance.DiscussionThe incidence of CRE infection was notably higher in the detected CRE group. Our study provides real-world evidence on the role of active CRE surveillance in survival outcomes, especially in regions like China, where CRE infections are highly prevalent. The findings suggest that active CRE surveillance could serve as an early indicator of 90-day mortality in hematology patients and should be considered for routine implementation in this population.